Antibiotic Susceptibility and Molecular Analysis of Bacterial Pathogen Pasteurella Multocida Isolated from Cattle - Azmat Jabeen, Mahrukh Khattak, Shahzad Munir, Qaiser Jamal, Mubashir Hussain (Journal of Applied Pharmaceutical Science, 2013)
Pasteurella multocida is a Gram negative, non motile and coccobacillus bacterium. It has 5 strains i.e. A, B, D, E and F and 16 serotypes (1-16). In present study, we analyzed Pasteurella multocida B: 2 strains, responsible for Hemorrhagic Septicemia (HS) in cattle, on morphological/microbial, biochemical, molecular level and to check the antibiotic sensitivity of the Pasteurella multocida. Microbial analysis showed that while grown on Brain Heart Infusion agar plates and Blood Agar Base Medium, grayish lustrous colonies of Pasteurella multocida were observed. Gram staining showed that Pasteurella multocida are gram negative. Microscopic observations revealed it to be coccobacillus and it was non- motile. Identification was conducted by conventional biochemical tests and percentage identification of Analytical Profile Index was 96 %. Antibiotic sensitivity with different antibiotics was checked by disk diffusion method and was found resistant to Augmentin, Amoxicillin and Aztreonam and was more susceptible to Ceftiofur. On molecular level its DNA was extracted and was run with marker having range from 0.5 – 10 kb. Its DNA was found heavier than 10 kb. It was concluded that accurate laboratory diagnosis of Pasteurella multocida depends on isolation and identification of suspected bacterial colonies by microscopy and biochemical tests. Molecular analysis is a successful tool for differentiation of strains in a variety of bacterial infections.
Keywords: Pasteurella multocida, Hemorrhagi